Effective Nitrogen Incorporation for High‐Potential Anthracene Cathodes with Conjugated Frameworks. Issue 9 (13th July 2022) - Kim, Yongju; Seol, Jae Seung; Jung, Ku Hyun; Han, Hyungu; Kim, Ki Chul
Abstract: To design high‐potential cathode materials for Li‐ion batteries through doping architecture, a well‐known anthracene framework is used as the basis for a broad array of nitrogen‐incorporated derivatives. A computational investigation of these derivatives clarifies that introduction of electron‐withdrawing nitrogen atoms improves the intrinsic redox potential at fully charged states, exhibiting a linear correlation between redox potential and electron affinity. However, this linear relationship between the redox potential and the density of nitrogen dopants is not fully followed during the discharging process. Consequently, it is found that doping one to three nitrogen atoms into anthracene is detrimental to the Li‐storage capacity, while doping four to ten nitrogen atoms is suggested as a suitable approach to improve the redox properties. At the end of the discharging process, electron affinity no longer plays a critical role in determining the redox potential. Each derivative is cathodically deactivated with the binding of the last Li atom, primarily owing to a sudden increase in the solvation energy, despite a negligible change in the electron affinity. These analyses assist to establish a promising approach for designing nitrogen‐incorporated anthracene derivatives for high‐performance cathode applications. Abstract : It is important to design redox‐active organic cathode materials with highly conductive nature for high‐performance secondary battery applications. In this study, a strategic design is pursued to highly electron‐conductive conjugating anthracene with the aim of optimizing its redox activity. The nitrogen‐incorporated anthracene derivatives are demonstrated to have a beneficial impact on their performance depending on the dopant density.